2014
DOI: 10.1177/011719681402300301
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction of the Families of Migrants in the Philippines

Abstract: Although remittance income is likely to increase the level of financial resources in the household, such a contribution should be assessed against the disruptive effect of migration on other aspects of family life. Using individual-level data from the Philippines, this article explores the impact of international migration on the life satisfaction of the families of migrants in the home country. The analysis compares happiness outcomes across non-migrant households, the households reliant on remittances as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Unfortunately, the issue related to the confiscation of workers' passports by overseas employers is still unaddressed. Therefore, in emigration, there are disruptive effects on both the emigrants themselves at their destination and on the family members left behind at home (Oh ). In the Indian context, there exists a knowledge gap of the actual impact of remittances on the well‐being of emigrants' family members.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the issue related to the confiscation of workers' passports by overseas employers is still unaddressed. Therefore, in emigration, there are disruptive effects on both the emigrants themselves at their destination and on the family members left behind at home (Oh ). In the Indian context, there exists a knowledge gap of the actual impact of remittances on the well‐being of emigrants' family members.…”
Section: Discussionmentioning
confidence: 99%
“…This kind of split household for an extended period of time is quite prevalent in many developing countries as a common economic livelihood strategy for many households (Mazzucato & Schans, 2011; Sulemana et al, 2019; Zentgraf & Chinchilla, 2012), in which one partner migrates for better opportunities, and another stays at home considering the uncertainty of employment opportunity and high cost of living in destination areas. This global phenomenon (Ivlevs et al, 2019; Perkins et al, 2011) is reflected in the context of transnational migration from Mexico to the United States (Heymann et al, 2009; Nobles et al, 2015) and from Africa to Europe (Mazzucato et al, 2015), as well as transnational and internal migration in Asian countries (Desai & Banerji, 2008; Gartaula et al, 2012; Liang, 2016; Lu, 2012; Nguyen et al, 2006; Oh, 2014; Paulone & Ivlevs, 2019). Studies on the impact of internal migration on Ghana and Chinese families have demonstrated that spatial separation of couples may increase the likelihood of divorce between the couple (Bhargava & Tan, 2018; Caarls & Mazzucato, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Whatever most of the research on migration has been done in economic development, economic growth and employment issues (Rahamanm, 2007) rather than their family perspective and life satisfaction of their family. Although remittance income maybe increases their financial condition in their household, such a contribution should be assessed against the disruptive effect of migration on other aspects of family life (Oh, 2014). Nevertheless, it's a debatable issue for the cause of migration but recent work on migration has been done in family perspective and their life satisfaction.…”
Section: Introductionmentioning
confidence: 99%